OP0271 To Aspirate or not to Aspirate: A Trainee Doctor's Dilemma. (10th June 2014) - Farah, Z.; Reddy, V.; Giles, I.
Abstract : Background: Patients with acute monoarthritis usually present to the accident and emergency department where a trainee doctor assesses them. Therefore, the initial management and likely patient outcomes are influenced by the trainee doctor's experience in the management of acute monoarthritis. Our previous work evaluating the clinical practice at two London teaching hospitals indicated a poor adherence to the BSR guidelines in the management of acute monoarthritis. We found that there was delay in specialist referral of hot swollen joints and that only 20/39 (51.3%) patients at centre 1 and 7/22 (31.8%) patients at centre 2 had a joint aspiration and only 30% had blood cultures performed prior to antibiotics. Objectives: We therefore set out to understand the trainee doctor's perspective on early management of acute monoarthritis including training in joint aspiration skills. Methods: A total of 140 trainees at both Trusts were surveyed. Of all 140 trainees, 29 (21%) were foundation year 2 doctors and 111 (79%) were specialty trainees (CMT, ACCS, GP VTS and Specialty Registrars). Trainees in specialties such as paediatrics, obstetrics and gynaecology and psychiatry were excluded. Data were collected regarding trainees' experience at arthrocentesis, the most common joints aspirated, their perceived degree of confidence at performing the procedure, and reasons for lack of confidence. We also surveyed their opinion regarding training for arthrocentesis. Results: A majority of respondents, 93 (67%), had aspirated at least 1 joint, half of whom had aspirated >4 joints mostly in a hospital setting. The most common joint aspirated was the knee (67%) followed by the shoulder (21%). However, 72 (52%) participants reported that they were not confident at aspirating a hot swollen joint and most of the rest commented that they were only confident at aspirating the knee. Further, as the main reason for the lack of confidence at joint aspiration, 58 (42%) participants reported an inadequate exposure, and 43 (31%) reported an inadequate training. Also, 37 (27%) respondents reported that they did not feel competent at performing the procedure whereas 30 (22%) preferred to refer to a specialist. Regarding blood cultures in a pyrexic patient, the overwhelming majority 131 (97.0%) opted that they would take blood cultures. Importantly, 101 (75%) respondents indicated that there should be more training in joint aspiration as part of the curriculum. Conclusions: Our data indicate that trainee doctors do not feel confident or competent at joint aspiration despite reasonable previous exposure, which may explain, at least in part, poor adherence to guidelines in clinical practice. We suggest that joint aspiration skill should be "upgraded" to an essential rather than desirable skill in the trainee doctor's curriculum to deliver focused training on arthrocentesis to improve management of acute monoarthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2732